1991
DOI: 10.1177/0146167291171016
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Vulnerability to Pregnancy and the Use of Effective Contraception

Abstract: A study was conducted to determine (a) whether the lower pregnancy risk that sexually active college women attribute to themselves relative to "average"others results from underestimating their own risk or overestimating others' risk and (b) the relationship of this perceived difference to contraceptive use. Sexually active women, on the average, accurately rated their own and their best friend's risk and overestimated others' risk, although users of poor contraception did tend to overestimate the effectivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(43 citation statements)
references
References 25 publications
5
37
1
Order By: Relevance
“…Do people judge themselves to be at lower risk relative to the average member of a large group (e.g., the students at their university) than relative to the average member of a small group (e.g., the students in their psychology class)? Although some existing research is consistent with this hypothesis (e.g., Whitley & Hern, 1991), confounding variables, such as the perceived closeness or similarity of the target group to oneself, need to be adequately controlled.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Do people judge themselves to be at lower risk relative to the average member of a large group (e.g., the students at their university) than relative to the average member of a small group (e.g., the students in their psychology class)? Although some existing research is consistent with this hypothesis (e.g., Whitley & Hern, 1991), confounding variables, such as the perceived closeness or similarity of the target group to oneself, need to be adequately controlled.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Perloff and Fetzer (1986) found that college students judged the risk for the average student and the average person to be greater than that of their closest friend, same-sex parent, and a sibling. Furthermore, subjects' judgments for the latter three targets did not differ significantly from their judgments of their own risk (see also Whitley & Hern, 1991). Klar et al (1996) have shown that this basic effect is observed even when the comparison individual is not a friend or relative of the subject.…”
mentioning
confidence: 87%
“…It tends to be smaller when the compar- ison other is an individual-especially a friend or relative of the participant-and larger when the comparison other is the average member of some group (Klein & Weinstein, 1997). Whitley and Hern (1991), for instance, found that college women judged their risk of an unwanted pregnancy to be about the same as that of their best friend, somewhat lower than that of the average college woman, and considerably lower than that of the average woman. Price (2001) has recently suggested that this might be a simple group size effect: Risk judgments increase as the size of the target group increases.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that individuals harbor pessimistic biases for others may represent a mechanism by which they maintain a comparatively optimistic outlook for themselves, despite realizing that health-related risks do increase with age. This might satisfy a need for accuracy by acknowledging more objective risk at an absolute level, but serve self-protective needs by maintaining a pessimistic view of others at the same time (Armor & Taylor, 1998;Whitley & Hern, 1991). The social network, be it real or imagined, can be seen as a convoy that moves through the life course and serves as a backdrop for self-serving social comparisons.…”
Section: Discussionmentioning
confidence: 99%